2003
DOI: 10.1046/j.1423-0410.2003.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of hepatitis B virus infection in patients with β‐thalassemia receiving multiple transfusions

Abstract: A high frequency of HBV infection was seen using molecular methods in thalassemic patients. The frequency of infection was similar in vaccine responders and non-responders. A number of mutations were observed in the S gene, which could have implications for viral replication as well as virus-host cell interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 33 publications
5
43
2
Order By: Relevance
“…In this study, occult hepatitis B infection detected by HBV-DNA testing constituted 32.4% of thalassemic children, which is similar to results from India [9] Table 3. Comparison between HCV-RNA, HBV-DNA and ANA of thalassemic patients included in the study in relation to age groups P-value is significant if < 0.05* Table 4.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, occult hepatitis B infection detected by HBV-DNA testing constituted 32.4% of thalassemic children, which is similar to results from India [9] Table 3. Comparison between HCV-RNA, HBV-DNA and ANA of thalassemic patients included in the study in relation to age groups P-value is significant if < 0.05* Table 4.…”
Section: Discussionsupporting
confidence: 89%
“…The true burden of HBV infection in the thalassemic population, using the more sensitive molecular detection methods, has not been estimated [9].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in studies in Jordon and Iran with measured HBsAg prevalence being 3.5% and 1.5% respectively indicating vaccination against Hepatitis B decreases the incidence of HBsAg positivity. 22 The low incidence of HBsAg positivity could be due to development of good antibody titre after vaccination. Ideally, a minimum of two doses of vaccination should be given before starting transfusion in a newly diagnosed thalassemia case.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HBV infection reported by various authors from India ranges from 2 to 69.2%. [74][75][76][77] An earlier report of 1995 had shown that 69.2% of thalassemic patients had HBV infection. 74 However, subsequent reports have however shown a lower prevalence of HBV infection in thalassemics.…”
Section: Transfusion Of Blood and Blood Productsmentioning
confidence: 99%